The Potential of Halal Food Business in Asia and Europe with Majority of Non-Muslim Communities - Ni'mah Izati Atiko Putri; Karseno Karseno; Dinda Khabibatul Fuadah; Haznah Munna Firdausi; Syifa Ulhusna; Mohammad Arief Bagus Prabowo (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2021)
The purpose of this article is to find out about how the halal food business is, what halal food restaurants are already in Asia and Europe, what is the potential of the Muslim community in Asia and Europe, and what is the potential of the halal food business in Asia and Europe with the majority non-Muslim society. In Islam, food is not only seen in terms of appearance and taste, but there are more important factors, namely whether the food is halal or not. The halalness of a food is very important as a consideration in the consumption of a food. The study results show that the halal food industry in Asia is increasing. The study results show that the halal food industry in Asia and Europe is increasing. The reason is, the existence of the Muslim population has increased growth, based on the trend of demand for halal products and also halal tourism. This is a great opportunity for business people to meet the demand for halal food. The challenge is how to improve quality and meet halal standards to meet consumer demand.